The concept of psychosocial risks at work - Sekil, Rokia (Journal of Human Sciences, 2023)
Psychosocial risks at work are an important part of the occupational risks that threaten the worker in the workplace, and which are caused by several psychological and social factors related to work pressures, and workers’ relationships with the employee, and with each other... and have negative effects on workers’ performance., and the institution, which is numerous and diverse: anxiety, depression, sexual and moral harassment, violence, alienation and psychological burnout... which constitute a major challenge in the field of health protection at work, both for employers, by providing the means to reduce exposure to Working for it, or for countries through the development of legislation to ensure its prevention, and to take care of those exposed to it, through this research we will try to clarify its concept by relying on the descriptive approach, with the aim of introducing it, and calling for attention to protection from it given its seriousness.